Relationship between the status of occupational health management and job satisfaction among farmers: A health promotion approach - Hesamedin Askari Majdabadi; Behzad Khadri; Elham Akhlaghi Pirposhteh; Mahdi Nouri; Zahra Abbasi Dolatabadi; Negin Kassiri; Milad Abbassi; Zahra Ghalichi-Zave; Mohsen Poursadeqiyan; Nasir Amanat; Ali Salehi Sahlabadi; Javad Vatani; et al. (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Job satisfaction is one of the most important issues related to human resources in the organization which can reduce organizational productivity. In this regard, occupational health is an important science related to the health of the workforce in any organization, paying attention to it will help health promotion. The aim of the present study was to determine the relationship between the status of occupational health management and job satisfaction among farmers with a health promotion approach. MATERIALS AND METHODS: This cross-sectional study was conducted in 2020. The number of 209 farmers from all villages of Zabol was included by census method. Data were collected using a researcher-made questionnaire that consisting of three sections of demographic information, occupational safety and health status, and standard job satisfaction questionnaire. At first, the validity and reliability of the questionnaire were evaluated. In addition, 5-10 staff working in Agricultural Jihad Organization were asked about the content, clarity, and simplicity of the questionnaire terms. Content validity index and content validity ratio indexes were calculated as 0.68 and 0.83 for occupational health management and 0.69 and 0.83 for job satisfaction questionnaires, respectively. Instrument reliability was also assessed using the Cronbach's alpha coefficient, which was 0.872. Finally, after verifying the validity and reliability of the instrument, a questionnaire was used to collect the research data. Shapiro-Wilk, Wilcoxon, and Spearman correlation tests were used to analyze the findings. The collected data were analyzed using SPSS software version 19. Armonk; NY, USA: IBM Corp. RESULTS: The results of the study indicate that occupational health management was at a moderate to a high level (3.701) and job satisfaction (3.381) was at a moderate to a high level. The standard regression coefficient between occupational health management and job satisfaction was obtained as 0.571. With a confidence of 95%, it can be stated that occupational health management in Zabol city under the supervision of jihad-e-agriculture organization has a significant impact on farmers' job satisfaction. In addition, the research findings confirmed a positive and significant relationship between occupational health management and job satisfaction of employed farmers and showed that the implementation of occupational safety and health programs in the jihad-e-agriculture organization can affect the job satisfaction of farmers. CONCLUSION: According to the evaluation of research findings, job satisfaction and occupational health management in the Agricultural Jihad Organization are relatively favorable among farmers in Zabol city. It was argued that there is a relationship between occupational health management and job satisfaction, that the implementation of programs related to occupational safety and health management system such as Health and Safety Executive will promote health.